2015
DOI: 10.1007/s11011-015-9733-6
|View full text |Cite
|
Sign up to set email alerts
|

Honey prevents neurobehavioural deficit and oxidative stress induced by lead acetate exposure in male wistar rats- a preliminary study

Abstract: This research sought to investigate the possible neuroprotective effects of honey against lead (Pb)-induced neurotoxicity. Twenty four male Wistar rats were divided into four groups: Control group that received 1 ml/kg distilled orally for 28 days; while groups II-IV received 0.2% lead in drinking water and 1 ml/kg of distilled water, 1 ml/kg of honey, 1.5 ml/kg of honey respectively for 28 days. Anxiety and exploratory activities were determined in the open field test. Memory function was determined using Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…It means that both extracts have ability to increase the antioxidant capacity to alleviate the effect of noise stress. Our results comparable with Abdul majeed et al [58] reported that honey (1.5 mL/kg b.w) decrease the lipid peroxidation level and enhanced the other antioxidant enzyme level on lead induced oxidative stress in wistar rat.…”
Section: Discussionsupporting
confidence: 91%
“…It means that both extracts have ability to increase the antioxidant capacity to alleviate the effect of noise stress. Our results comparable with Abdul majeed et al [58] reported that honey (1.5 mL/kg b.w) decrease the lipid peroxidation level and enhanced the other antioxidant enzyme level on lead induced oxidative stress in wistar rat.…”
Section: Discussionsupporting
confidence: 91%
“…While both the tests for open field and Morris water showed results of positive neuroprotection effects of the honey, its MDA results showed no significant change between the groups. The results of antioxidant activities (catalase, SOD and GSH) however coincides with the results from the study by Azman et al, 2018 showing a significant increase in honey treated animals with the rats given 1.5 mL/kg honey better results compared to the lower dosed honey (Azman et al 2018;Abdulmajeed et al 2016). In another study, stinglees bee honey significantly increases lymphoblastic cell viability by more than 150%.…”
Section: Effect Of Honey On Brain: Possible Mechanismsupporting
confidence: 84%
“…Results have mostly led to an increase of the free radicals causing this imbalanced condition. Honey have shown to attenuate with damage resulting from oxidative stress (Sairazi et al 2017;Ranneh et al 2019;Azman et al 2018;Abdulmajeed et al 2016).…”
Section: Effect Of Honey On Brain: Possible Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…[127,128] Organic compounds having antioxidant and free radical scavenging activity in honey composition shows that it keeps the ability to work in human nutrition as a vital source of antioxidants. [129] Besides, as far as antiinflammatory effect of honey is concerned, it causes a drop in necrosis tissues.…”
Section: Antioxidant Potentialmentioning
confidence: 99%